Hubungan Tingkat Stres dengan Kualitas Tidur pada Mahasiswa Prodi Sarjana Terapan Farmasi: The Relationship between Stress Level and Sleep Quality in Students of Applied Pharmacy Undergraduate Study Program - Nur Khalifah Rahmadhani; Ismail Ibrahim; Ida Adhayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
A person's sleep quality is said to be good if he does not show various symptoms of sleep deprivation and does not experience problems in his sleep. Sleep deprivation conditions are also common among students. Students have demands to do presentation assignments, test preparation. Final year students are required to complete their final project, namely a thesis as a condition for obtaining a bachelor's degree. Students can experience stress when working on a thesis caused by several factors such as difficulty in expressing thoughts in written form, pressure from parents to graduate quickly and being lazy in doing thesis. So that students are a group at risk of having poor sleep quality. This type of research is a quantitative descriptive study, with a cross-sectional research design where this research was conducted using an online questionnaire that aims to determine the relationship between stress levels and sleep quality in undergraduate students of the Applied Pharmacy Study Program. The number of samples in this study were 84 people. Based on the results of the study, it was obtained that the average value of sleep quality for Pharmacy students from the Health Polytechnic of the Ministry of Health Makassar was 14.35 which was in the bad interval and the stress level was in the moderate interval range with an average value of 20.11. Based on the Chi-Square test, the value is 0.002 and the Correlation Coefficient is 0.295, which means that there is a relationship between sleep quality and stress levels. ABSTRAK Kualitas tidur seseorang dikatakan baik jika tidak menunjukkan berbagai gejala kekurangan tidur dan tidak mengalami masalah dalam tidurnya. Kondisi kurang tidur pun biasa ditemui pada kalangan mahasiswa. Mahasiswa memiliki tuntutan untuk mengerjakan tugas presentasi, dan persiapan ujian. Mahasiswa tingkat akhir dituntut untuk menyelesaikan tugas akhirnya yaitu skripsi sebagai syarat untuk memperoleh gelar sarjana. Mahasiswa dapat mengalami stres ketika mengerjakan skripsi disebabkan oleh beberapa faktor seperti, kesulitan menuang pikiran dalam bentuk tulisan, tekanan dari orang tua agar cepat lulus dan malas dalam mengerjakan skripsi. Oleh karena itu mahasiswa merupakan kelompok yang berisiko memiliki kualitas tidur yang buruk. Jenis penelitian ini adalah penelitian deskriptif kuantitatif, dengan desain penelitian cross sectional dimana penelitian ini dilakukan dengan kuesioner online yang bertujuan untuk mengetahui Hubungan Tingkat Stres dengan Kualitas Tidur Pada Mahasiswa Prodi Sarjana Terapan Farmasi Poltekkes Kemenkes Makassar. Jumlah sampel pada penelitian ini sebanyak 84 orang. Berdasarkan hasil penelitian diperoleh nilai rata-rata kualitas tidur pada mahasiswa Farmasi Poltekkes Kemenkes Makassar yaitu 14,35 yang bearada pada interval buruk dan tingkat stres berada pada range interval sedang dengan nilai rata-rata 20,11. Berdasarkan uji Chi-Square didapatkan nilai 0,002 dan Correlation Coefficient didapatkan nilai 0,295 yang berarti terdapat hubungan antara kualitas tidur dengan tingkat stres.